Inventarisasi Data Pengetahuan (Ontologi) Dalam Upaya Penyusunan Kompendium Keilmuan Komunikasi Hindu Berbasis Budaya - Ni Gusti Ayu Ketut Kurniasari; I Wayan Budha; Untung Suhardi; Anak Agung Ketut Patera; I Wayan Arif Sugiarta; Wayan Tantre Awiyane (Jayapangus Press, 2022)
Industrial development 4.0 and 5.0 who moved so fast bring curriculum changes in policy direction. However, of the curriculum change independent learning independent campus bring their own special characteristics culture, on the local wisdom and digitalisasi. The theory used in this research was vakyapadia, rasa theory and theory of computer mediated communication. Using paradigm critical and methods of using vakyapadiya linguistic analysis, data collection through study library and forum groub discussion. Research findings curriculum is based design culture culture; existence as a basis for curriculum design, the vedas as philosophical curriculum design, harmonisation as a purpose in the design, curriculum and Brahman as a source of knowledge and object characteristic hindu communication. In addition, cultural values and the philosophical hindu became the basis in the design independent curriculum learning campus independent and be the reference in the vedas philosophical developed the theory hindu communication based scientific culture.